Orbital Angular Momentum Pattern Synthesis via Convex Optimization - Wang, Jing; Ding, Haibing; Guo, Naining; Cai, Yang; Xue, Qianzhong (IEEE antennas and wireless propagation letters, 2025)
This letter presents an effective optimization synthesis approach for orbital angular momentum (OAM) beams with low sidelobe and high mode purity through antenna array complex excitation optimization. The optimal synthesis is formulated as minimizing a linear function of the real and the imaginary parts of the array excitations on a convex set, expressed as a convex programming problem. Besides, two simplification methods are introduced to reduce computational complexity and enhance efficiency. Numerical experiments involving diverse array boundary configurations, element arrangements, OAM mode numbers, and complex pattern mask cases are performed, and the results validate the flexibility, effectiveness, and broad applicability of the proposed approach.